Реализация информационной технологии прогнозирования процессов развития макроэкономической системы - Гринченко, Марина Анатольевна (Харківський університет Повітряних Сил ім. І. Кожедуба, 2011)
Рассмотрены вопросы разработки информационной технологии прогнозирования процессов развития макроэкономической системы. Выделены основные принципы создания и внедрения информационно- аналитических СППР для управления региональной макроэкономической системой. Разработана функциональная структура СППР. Представлены результаты реализации информационной технологии прогнозирования на примере данных Харьковской области.

The questions of development of information technology of prognostication of processes of development of the macroeconomic system are considered. Basic principles of creation and introduction of informaciyno-analitichnikh SPPR are selected for a management the regional macroeconomic system. The functional structure of SPPR is developed. The results of realization of information technology of prognostication on the example of information of the Kharkov area are presented.
Realization of information technology of prognostication of processes of development of macroeconomic system. Research results
Keywords: система поддержки принятия решений; природные ресурсы; сельское хозяйство; интеллект общества; динамика изменения ВВП; управленческие решения; information technology; prognostication; macroeconomic system; processes of development; system of support of making a decision